Car Engine Storage and Spare Parts Management System Using RFID Technology - Evizal Abdul Kadir; Siti Mariyam Shamsuddin; Sri Listia Rosa (IAES Indonesia Section, 2015)
very year, demanding of spare parts for vehicle isincreasing together to the number of cars, thus spare parts toreplacing faulty component also high demand. Every workshopneed to keep spare parts for replacing breakdown vehicle or someworkshop request spare parts to store it. Base on that, a good spareparts management and storage system is required for effective andfaster service to thecustomer. This paper discuss on the use ofRadio Freqeuncy Identification (RFID) for car engine storage andspare parts management system using RFID technology, because ofits advantages compare to others technology which is no line ofsight required and multiple reading. Every spare parts or enginetagging by an RFID tag which is programmed early with uniqueidentity, then store to a central database for stock and inventorysystem. Testing havebeen conducted an shows reduce on reading performance becauseof most spare parts and engine made from metal material thuseffected to RFID reading performance. A new technique used forRFID tag before tagging which is make some gap from the engineor spare parts to avoid RFID signal absorve by metal material. Theother way is used high gain antenna andRFID reader for faster and powerfull reading. Results showsimprovement on reading distance and performance compare to theprevious tagging technique and tagging placement.